PENERAPAN MODEL SERVICE LEARNING DALAM MENINGKATKAN HASIL BELAJAR DI SMA NEGERI 15 PANGKEP - Mustamin; Nurlaelah; Akil, M; Wahab, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the Service Learning learning model in improving students’ learning outcomes in Islamic Religious Education for class XI at SMA Negeri 15 Pangkep. The research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The subjects of this study were 33 eleventh-grade students. Data collection techniques included observation, tests, interviews, and documentation. The results showed that the implementation of the Service Learning model was able to improve students’ learning outcomes. In the pre-cycle stage, only 30.30% of students achieved learning mastery. After the implementation of the Service Learning model in cycle I, the percentage of learning mastery increased to 64%, and in cycle II it improved further until it reached the predetermined success criteria. In addition to improving learning outcomes, the Service Learning model also enhanced students’ activeness, learning motivation, cooperation, and social awareness in the Islamic Religious Education learning process. Therefore, the Service Learning learning model can be used as an effective and innovative alternative in improving the quality of Islamic Religious Education learning.